2021
DOI: 10.3390/jcm11010125
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency in Heart Failure: Mechanisms and Pathophysiology

Abstract: Iron is an essential micronutrient for a myriad of physiological processes in the body beyond erythropoiesis. Iron deficiency (ID) is a common comorbidity in patients with heart failure (HF), with a prevalence reaching up to 59% even in non-anaemic patients. ID impairs exercise capacity, reduces the quality of life, increases hospitalisation rate and mortality risk regardless of anaemia. Intravenously correcting ID has emerged as a promising treatment in HF as it has been shown to alleviate symptoms, improve q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 286 publications
(433 reference statements)
0
47
1
Order By: Relevance
“… Iron deficiency is a frequent comorbidity in heart failure, present in approximately 30–50% of patients and is associated with worse long-term outcomes [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“… Iron deficiency is a frequent comorbidity in heart failure, present in approximately 30–50% of patients and is associated with worse long-term outcomes [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although our understanding of iron deficiency (ID) in heart failure (HF) has been evolving from merely a prevalent comorbidity that is associated with worse clinical course to an important player in disease progression that can be modified, many questions remain to be answered 1 . In the most recent HF guidelines of the European Society of Cardiology (ESC) of 2021, it is suggested that haemoglobin and iron status should be checked periodically in all HF patients 2 .…”
Section: Figurementioning
confidence: 99%
“…The mechanisms of the spontaneous resolution could be explained by the initial aetiology of ID. For this several hypotheses have been proposed, including reduced dietary intake, decreased iron uptake due to inflammation and impaired intestinal function, and increased loss of iron as a result of occult gastrointestinal bleeding 1 . Some of these might alter over time, while others are persistent in nature.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations